International Trade in Health Services and the GATS : Current Issues and Debates - Blouin, Chantal; Drager, Nick; Smith, Richard (Washington, DC: World Bank, 2012)
Health ministries around the world face a new challenge: to assess the risks and respond to the opportunities of the increasing openness in health services under the World Trade Organization's (WTO) General Agreement on Trade in Services (GATS). This publication addresses this challenge head-on by providing analytical tools to policymakers in health and trade ministries alike who are involved in the liberalization agenda and, specifically, in the GATS negotiations. This book informs and assists policymakers in formulating trade policy and negotiating internationally. There is ongoing and animated international debate about the impact of GATS on public services in general and health in particular. In response, the book offers different perspectives from more than 15 leading experts. Some of the authors stress opportunities linked to trade in health services, others focus more on the risks. The book offers: Detailed legal analysis of the impact of the agreement on health policy; an overview of trade commitments in health-related services; new empirical evidence from nine country studies; and a simple 10-step explanation on how to deal with GATS negotiations.